Plasmonic organic bulk–heterojunction solar cells based on hydrophobic gold nanorod insertion into active layers. Issue 9 (30th October 2017) - Liu, Zhihai; Wang, Tuntun; Nanda, Sitansu Sekhar; Yi, Dong Kee; Lee, Eun‐Cheol
ABSTRACT: In this work, we fabricated plasmonic organic bulk–heterojunction solar cells by inserting hydrophobic gold nanorods (GNRs) into the active layers. Power conversion efficiency was improved from 7.43% to 8.22% because the plasmonic effect of GNRs improved the light harvesting efficiency. Maximum exciton generation rate was increased from 1.35 × 10 −26 to 1.51× 10 −26 m −3 s −1, and the electron mobility was also increased from 8.6 × 10 −5 to 1.5× 10 −4 cm −2 V −1 s −1 . As a result, the short circuit current density was improved from 15.5 to 16.7 mA cm −2 —the dominant reason for performance enhancement. The open circuit voltage and fill factor were improved simultaneously. The plasmonic device showed a highest PCE of 8.43%, indicating that doping GNRs into active layers is a simple and effective way to fabricate high‐performance organic solar cells. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45920. Abstract :